(untitled) (The Agriculturists, 2010)
Broiler parent stock of 7851 Cobb-500, 8388 Ross and 8745 Hubbard-Hi-Yield were reared in controlled (slated cum floor system) house to determine the egg production performance, fertility and hatchability. A total of 151200 hatching eggs of Cobb-500, Ross and Hubbard-Hi-Yield broiler strain were collected and set in the incubator in 10 batches having 15120 eggs in each batch and 5040 eggs in each strain to compare fertility and hatchability among the strains. From the above study, it was observed that the strains had significant effect (P<0.01) on egg production, fertility and hatchability of fertile, and set eggs, abnormal chicks, egg and chick weight but there was no significant effect (P>0.05) on normal chick production and chick weight as percentage of egg weight. Hubbard-Hi-Yield strain was the best while Ross was intermediate and Cobb-500 was the poorest in terms of egg production, fertility and hatchability. Therefore, Hubbard-Hi-Yield broiler parent stocks as well as its grand parent stock may be more profitable and suitable for broiler production in Bangladesh.